1997
DOI: 10.1136/emj.14.4.219
|View full text |Cite|
|
Sign up to set email alerts
|

Prehospital emergency rapid sequence induction of anaesthesia.

Abstract: Objective-To determine the number of and reasons for rapid sequence inductions done by accident and emergency (A&E) doctors out of hospital as part of the activities of the MEDIC 1 Flying Squad. "Rapid sequence induction" was defined as any attempted endotracheal intubation accompanied by use of drugs to assist intubation and ventilation, including opiates, benzodiazepines, intravenous and topical anaesthetics, and neuromuscular blocking drugs. Methods-Retrospective study of ali MEDIC 1 and A&E records over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…A group of emergency physicians previously reported diYculty intubating 65% of trauma patients in the prehopsital setting. 11 These patients all had a hard cervical collar in situ. Although the emergency physicians in our series seemed to experience more diYculty performing intubation than anaesthetists, the number of repeated attempts at intubation was < 2%, which is much lower than in previously documented reports.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A group of emergency physicians previously reported diYculty intubating 65% of trauma patients in the prehopsital setting. 11 These patients all had a hard cervical collar in situ. Although the emergency physicians in our series seemed to experience more diYculty performing intubation than anaesthetists, the number of repeated attempts at intubation was < 2%, which is much lower than in previously documented reports.…”
Section: Discussionmentioning
confidence: 97%
“…The only other British study documenting the use of prehospital RSI involved a much smaller number of patients, in whom an array of sedative agents was used. 11 No details of haemodynamic parameters were given. The use of neuromuscular block in the prehospital setting is well established 7 8 10 and has been shown to be associated with few complications.…”
Section: Discussionmentioning
confidence: 99%
“…Prehospital difficult intubation is poorly defined in the prehospital environment and the incidence has been reported to be between 5% and 50% 15. A previous study by emergency physicians5 reported difficulty with 65% of trauma patients in the prehospital setting; however, all these patients had a hard collar in situ. When difficult tracheal intubation is more precisely defined using the intubating difficulty score, the reported incidence is lower (16%) in prehospital emergency medicine 19.…”
Section: Discussionmentioning
confidence: 98%
“…Prehospital anaesthesia also allows the prehospital team to manage agitated patients better, such as those with head injuries and a relatively high Glasgow coma scale score 4. Although there is evidence that RSI in the prehospital setting can be performed safely when carried out by properly trained practitioners59 the risks are well recognised 10 – 14…”
mentioning
confidence: 99%
“…Several studies have demonstrated a low incidence of complications and an increase in intubation success rates with RSI. [7][8][9][10][11][12][13] Midazolam is commonly used as a sedative agent for RSI due to its rapid onset of action and favorable hemodynamic profile. [14][15][16] Multiple studies have demonstrated it to be relatively safe in euvolemic patients or in the presence of continuous hemodynamic monitoring for early detection of hypotension, such as in the operating room or intensive care unit.…”
mentioning
confidence: 99%